(untitled) (INNOVATIVE ECONOMY, 2023)
Khalatur S.M., Vodolazska O.A., Solodovnykova I.L., Tytarenko A.V. MANAGEMENT OF CREDIT POLICY FORMATION OF A COMMERCIAL BANK IN MODERN CONDITIONS Purpose. The purpose of the article is to substantiate the prerequisites, management components of the formation of the credit policy of a commercial bank and the main elements of the organizational support of this process in modern conditions. Research methodology. The theoretical and methodological basis of the research is the fundamental provisions of general economic theories, general theories of development. In order to achieve the set goal in the work, in particular, to determine the directions of improvement of the credit policy formation management of a commercial bank, the methods of analysis, synthesis and generalization are applied. A systematic method was used to justify proposals for reducing the credit risk of commercial banks. Series of dynamics, average values, comparison, graphic methods are used in the evaluation of the loans dynamics; estimates of the amount of loans granted to non-financial corporations by types of economic activity and repayment terms; estimates of loans granted to households by target direction and repayment terms. Findings. It stands to reason that commercial banks are facing unprecedented credit risk challenges as the financial market becomes increasingly volatile. It is justified that commercial banks, as financial institutions with the most influence, the largest number and the widest reach in the financial market, play a variety of roles, including financing money capital, directing capital flows and regulating the balance of public demand and supply. It is determined that as economic globalization continues to deepen, banks face increasingly tougher competition and this makes it difficult to accurately assess credit risk. Originality. The main elements of organizational support for the process of managing the formation of the credit policy of a commercial bank in modern conditions are defined. Practical value. The theoretical and methodological provisions of this study deepen the practical toolkit of the management of the formation of the credit policy of a commercial bank in modern conditions. Key words: credit, risk, management, development, control.